Parked on the verge: vocational rehabilitation of long-term unemployed citizens - a mixed methods study - Lotte Nygaard Andersen; Mette Jensen Stochkendahl; Kirsten K. Roessler (BMC, 2022)
Abstract Background Vocational rehabilitation programs (VRP) developing and improving work ability are used in Denmark to assist long-term unemployed citizens with complex problems. The aims of this study were to (1) describe VRP-participants in relation to general health, well-being, work ability and self-efficacy at baseline and one-year follow-up, (2) obtain an understanding of VRP-participants' personal development towards improving work ability, and (3) explore VRP-participants' hopes and thoughts about their future. Methods In a mixed methods approach, data from a longitudinal survey and semi-structured interviews were collected. In the quantitative longitudinal survey, all participants completed paper questionnaires at baseline and one-year follow-up. For the qualitative semi-structured interviews, VRP participants were recruited with a maximum variation sampling strategy through VRP coordinators and personal contact. Data were analysed by descriptive statistics and systematic text condensation. Following analysis, data were merged and presented in combination according to identified themes. Results At baseline and one-year follow-up 146 (response rate 34%) and 74 participants (response rate 52%) respectively, responded to the questionnaire. Seven participants were interviewed. The analysis revealed four themes: 1) Individual explanations of life situation and health; 2) Finding the path; 3) Work as giving meaning to life; 4) Hope for the future. Despite self-reported scores indicating poor general health, lack of well-being, low work ability and low self-efficacy, VRP-activities seemed to have assisted participants in finding meaning in life. VRP-components that may be drivers of successful recovery processes were identified. Conclusions VRP-participants experienced life situations that include multifactorial burdens, and low levels of general health, well-being, work ability, and self-efficacy at baseline and 1 year later. From the outset, most did not have a clear goal of employment, but over time, new goals were set as realistic opportunities for re-developing their work ability were explored. Successful core components of VRP were individually tailored programs and support, development of new relationships, and accommodated flexible internships and jobs. Trial registration ClinicalTrials.gov Identifier: NCT02641704 , date of registration December 29, 2015.